What's wrong with democracy? : from Athenian practice to American worship - Samons, Loren J., II (University of California Press, 2004)
In this daring reassessment of classical Athenian democracy & its significance for the United States today, Samons firstly shows why the Athenian model was distrusted by America's founding father, before considering how the concept of democracy has now become an object of popular veneration.